The impact of social media on library and information studies students at the University of Ibadan, Nigeria (2018)
The significance of social media in the teaching and learning process cannot be overemphasized. However the excessive use of the same can result into inefficiency and poor academic performance. The study examines the impact of social media (SM) on Library and Information Studies students at the University of Ibadan, Nigeria. The study adopted the descriptive survey research design. Questionnaire was used for data collection. 100 copies of questionnaire were distributed to the librarians in training at the Department of Library, Archival and Information Studies, University of Ibadan. 99 copies were filled and returned, given a response rate of 99%. Data generated were analyzed using descriptive statistics. The findings revealed that Whatsapp was the most preferred social media platform used more frequently by the LIS undergraduates. Majority of the students make use of SM more for other activities than academics, they spend 7 hours each day on the SM on general activities other than course work as against 5 hours spent each day for course work on the media, and as a result this undoubtedly affects their performance